Magnet with adhesive layer, manufacturing method thereof and manufacturing method of magnet assembly
Patent Information
- Application Number
- JP2023540129
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-12-29
- Filing Date
- 2021-10-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-10-26
Smart Images

Figure 0007635388000004 
Figure 0007635388000005 
Figure 0007635388000001
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of magnet manufacturing, and more particularly to magnets having an adhesive layer, a manufacturing method and a method for manufacturing a magnet assembly. [Background technology]
[0002] Permanent magnet motors have a simpler structure than conventional armatures and are characterized by their light weight, small size, low loss, and high efficiency, and their range of applications is extremely wide. Embedded magnet type permanent magnet motors have a higher torque density than surface magnet type permanent magnet motors.
[0003] In embedded magnet permanent magnet motors, magnets are fixed in the housing of the rotor or stator of the motor or generator by bonding them with a liquid adhesive. In general, a magnet body coated with the liquid adhesive is inserted into the housing of the rotor or stator, or the liquid adhesive is applied to the opening of the housing, and the magnet body is inserted through the opening of the housing containing the liquid adhesive, and the liquid adhesive is then applied to the surface of the magnet body. The rotor or stator is then left at room temperature or left in a drying oven to harden the liquid adhesive and bond the magnet to the rotor or stator.
[0004] However, in the above-mentioned bonding method, since the liquid adhesive before hardening has adhesiveness, it is easy for the magnet to get caught on the opening or inner wall of the container during movement. That is, the adhesive inadvertently comes into contact with the container before the magnet reaches the desired position in the container. In addition, since the liquid adhesive is soft before hardening, there is a problem that it deforms during the process of entering the container or partially peels off from the magnet body, so that most of the applied liquid adhesive does not enter the container, causing poor adhesion. There is also a problem that the workability of scraping off or wiping off the overflowing liquid adhesive before hardening is poor. Another issue is how to transport and store magnets that have been coated with a liquid binder in advance without losing the function of the binder.
[0005] To solve the above problems, in CN110401277A, after applying an adhesive containing an expansion agent to the surface of a magnet body, a first heating process is carried out to harden part of the adhesive first, reducing the viscosity of the adhesive surface, and also causing the expansion agent in the adhesive to protrude to the surface, bringing the adhesive into point contact with the tank, thereby avoiding the adhesive accidentally getting into the storage tank or peeling off and causing the adhesive to peel off.
[0006] In Patent Document JP2007174872A, a solid resin at room temperature is selected, a foaming agent is added to prepare a foam sheet, and when this is inserted into the gap between the magnet and the container and heated, the foam sheet expands and one side of the sheet adheres to the outer surface of the magnet and the other side of the sheet adheres to the inner wall of the container, thereby preventing the resin from being pushed out of the module container and leaking.
[0007] The problem of poor adhesion can be solved by lowering the viscosity of the adhesive or by adding a foaming agent to the adhesive to prepare a foam sheet, which is then directly inserted into the gap. However, the method of reducing the viscosity makes the adhesive layer soft, which makes it inconvenient to store or transport for a long time. The method of adding a foaming agent to the adhesive to process it into a foam sheet requires processing to improve compatibility depending on the size of the magnet or storage tank, which makes it difficult to process.
[0008] Summary of the Invention The present invention has been made in consideration of the problems in the background art described above, and its object is to provide a magnet having an adhesive layer that can easily be stored, transported, and attached to a carrier, a method for manufacturing the same, and a method for manufacturing a magnet assembly.
[0009] A magnet with an adhesive layer according to one embodiment of the present invention includes a magnet base and at least one adhesive layer arranged on a surface of the magnet base, the adhesive layer including a thermosetting adhesive layer and a thermoplastic adhesive layer, the thermosetting adhesive layer being closer to the surface of the magnet base than the thermoplastic adhesive layer, and the thermosetting adhesive layer including an expansion agent.
[0010] According to some embodiments of the present invention, the number of adhesive layers is a plurality of layers, and the plurality of adhesive layers are successively arranged outward from the surface of the magnet base; the ratio of the thickness of the outermost thermoplastic adhesive layer to the thickness of any one of the remaining thermoplastic adhesive layers is 2:1 to 8:1.
[0011] According to some embodiments of the present invention, the total thickness of the adhesive layer is between 80 and 150 μm.
[0012] According to some embodiments of the present invention, the ratio of the sum of all thicknesses of the thermosetting adhesive layers to the sum of all thicknesses of the thermoplastic adhesive layers is between 4:1 and 10:1.
[0013] According to some embodiments of the present invention, the thermoplastic adhesive layer includes a first coagent including nano barium sulfate and nano ethylene wax.
[0014] According to some embodiments of the present invention, the thermosetting adhesive layer includes a curing agent, a filler, and a second coagent, where the curing agent is at least one of guanidine, substituted guanidine, aromatic amine, and guanylamine derivative; the filler is at least one of silica, calcium oxide, zinc oxide, magnesium oxide, alumina, calcium carbonate, and talc; and the second coagent is at least one of a curing accelerator, a coupling agent, an antifoaming agent, a fiber, a rubber particle, a diluent, and a flame retardant.
[0015] Some embodiments of the present invention provide a method for manufacturing a magnet with an adhesive layer, comprising the steps of: preparing a raw material for a thermosetting adhesive layer by mixing an expanding agent into a thermosetting adhesive; and sequentially applying at least one adhesive layer from the surface of a magnet base outward, the adhesive layer comprising one thermosetting adhesive layer and one thermoplastic adhesive layer, the thermosetting adhesive layer being adjacent to the surface of the magnet base relative to the thermoplastic adhesive layer, the thermosetting adhesive layer being subjected to a low-temperature surface drying treatment, and the thermoplastic adhesive layer being subjected to a low-temperature curing treatment.
[0016] According to some embodiments of the present invention, the total thickness of the adhesive layer is between 80 and 150 μm.
[0017] According to some embodiments of the present invention, when the adhesive layer is applied in multiple layers in the application step, the ratio of the thickness of the outermost thermoplastic adhesive layer to the thickness of any remaining thermoplastic adhesive layer is 2:1 to 8:1.
[0018] According to some embodiments of the present invention, the ratio of the sum of all thicknesses of the thermosetting adhesive layers to the sum of all thicknesses of the thermoplastic adhesive layers is between 4:1 and 10:1.
[0019] According to some embodiments of the present invention, before the coating step, a monomer for synthesizing a thermoplastic base agent, an initiator, and a first auxiliary agent are mixed into distilled water as raw materials for the thermoplastic adhesive layer.
[0020] According to some embodiments of the present invention, when there is only one thermosetting adhesive layer, the thermosetting adhesive layer is formed by applying the raw material of the thermosetting adhesive layer multiple times.
[0021] According to some embodiments of the present invention, before the preparation step, the foaming agent is pretreated with a monomer that synthesizes a thermoplastic base agent; during preparation, the pretreated foaming agent is mixed into the thermosetting adhesive to form a raw material for the thermosetting adhesive layer.
[0022] One embodiment of the present invention provides a method for manufacturing a magnet assembly manufactured using a carrier and a magnet with an adhesive layer as described above, the method including an inserting step of inserting the magnet with an adhesive layer into a container of the carrier, a heating step of heating the carrier, and a heating step of expanding the expansion agent, crosslinking and curing the thermosetting adhesive layer, blending and copolymerizing the thermosetting adhesive layer with the thermoplastic adhesive layer, and filling the space between the container wall of the carrier and the magnet base with the heated adhesive layer.
[0023] The magnet with adhesive layer of the present invention is easy to store and transport by subjecting the thermosetting adhesive layer to low-temperature surface drying treatment and the thermoplastic adhesive layer to low-temperature curing treatment; it is also found that the expansion agent in the thermosetting adhesive layer maintains its original expansion ability even after long-term storage. By subjecting the thermosetting adhesive layer to low-temperature surface drying treatment and the thermoplastic adhesive layer to low-temperature curing treatment, it is possible to prevent the adhesive from deforming or becoming unevenly distributed when inserting the soft adhesive into the carrier storage tank, making it easy to bond the magnet to the carrier. [Brief description of the drawings]
[0024] In order to more clearly describe the technical solution of the present invention, the following briefly introduces drawings necessary for the description of the embodiments. Obviously, the drawings in the following description are only some embodiments of the present invention, and other drawings can be derived from these drawings for those skilled in the art without exceeding the scope of the claims of the present invention. [Figure 1] FIG. 1 is a schematic diagram of a magnet with an adhesive layer according to an embodiment of the present invention; [Diagram 2] FIG. 2 is a schematic diagram 2 of a magnet with an adhesive layer according to an embodiment of the present invention.
[0025] Specific embodiments The technical solutions of the present invention will be described below clearly and completely with reference to the drawings in the embodiments of the present invention, but obviously, the described embodiments are only some of the embodiments of the present invention, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive work belong to the protection scope of the present invention. [Figure 1] As shown in Figure 1, the present invention provides a magnet with an adhesive layer. The magnet with an adhesive layer comprises a magnet base 1 and an adhesive layer 2. The magnet base 1 is made of a magnetic material such as a neodymium iron boron magnet. [Diagram 2] As shown in Figure 2, the present invention provides a magnet with an adhesive layer. The magnet with an adhesive layer comprises a magnet base 1 and an adhesive layer 2. The magnet base 1 is made of a magnetic material such as a neodymium iron boron magnet.
[0026] The adhesive layer 2 is composed of a thermosetting adhesive layer 21 and a thermoplastic adhesive layer 22. The thermosetting adhesive layer 21 is mainly composed of a thermosetting adhesive, and contains an expansion agent 21a. The expansion agent 21a in the thermosetting adhesive layer 21 expands at a certain temperature, and the adhesive of the thermosetting adhesive layer 21 hardens. The thermoplastic adhesive layer 22 is a thermoplastic adhesive that hardens easily at low temperatures. In each adhesive layer 2, the thermosetting adhesive layer 21 is closer to the surface of the magnet base 1 than the thermoplastic adhesive layer 22.
[0027] The number of adhesive layers 2 is at least one. The first adhesive layer is provided on the surface of the magnet base body 1. When there is only one adhesive layer 2, the first adhesive layer becomes the entire adhesive layer, a thermosetting adhesive layer 21 is provided on the surface of the magnet base body 1, and a thermoplastic adhesive layer 22 is provided on the thermosetting adhesive layer 21 to form a magnet with adhesive layers.
[0028] The magnet with adhesive layer of the present invention has at least one adhesive layer provided from the surface of the magnet base to the outside, and the thermoplastic adhesive layer is cured under conditions of 40 to 90°C to form a non-adhesive thin layer, which protects the thermosetting adhesive layer and facilitates storage and transportation at room temperature. When the magnet body with adhesive layer is heated to 150 to 200°C, the thermoplastic adhesive layer softens, the expansion agent in the uncured thermosetting adhesive layer expands, and the binder in the gradually expanded thermosetting adhesive layer ruptures the thermoplastic adhesive layer and wraps the ruptured thermoplastic adhesive layer. At 150 to 200°C, the binder in the thermosetting adhesive layer self-crosslinks and hardens, and at the same time copolymerizes with the thermoplastic adhesive layer to form a stable crosslinked structure.
[0029] According to an alternative embodiment of the present invention, when the number of adhesive layers 2 is multiple, the multiple adhesive layers 2 are arranged in sequence from the surface of the magnet base body 1 toward the outside. In this application, multiple layers means two or more layers.
[0030] The multi-layer adhesive layer 2 is formed by alternately arranging thermosetting adhesive layers 21 and thermoplastic adhesive layers 22 from the surface of the magnet base 1 toward the outside. After applying the thermosetting adhesive layer 21, the thermoplastic adhesive layer 22 is applied, and after applying the thermosetting adhesive layer 21 again, the thermoplastic adhesive layer 22 is applied, and so on.
[0031] As shown in Figure 2, there are two adhesive layers 2, with a first thermoplastic adhesive layer 21 located on the surface of the magnet base body 1, a first thermoplastic adhesive layer 22 located on the first thermoplastic adhesive layer 21, a second thermoplastic adhesive layer 21 located on the first thermoplastic adhesive layer 22, and a second thermoplastic adhesive layer 22 located on the second thermoplastic adhesive layer 22.
[0032] When the number of adhesive layers 2 is multiple, that is, when the number of thermosetting adhesive layers and thermoplastic adhesive layers are both multiple, the thickness of each thermosetting adhesive layer is equal, the thickness of the remaining thermoplastic adhesive layers excluding the outermost thermoplastic adhesive layer is equal, and the ratio of the thickness of the outermost thermoplastic adhesive layer to the thickness of any remaining thermoplastic adhesive layer is 2:1 to 8:1. For example, when there are two thermosetting adhesive layers and two thermoplastic adhesive layers, the thickness of the second thermoplastic adhesive layer is 2 to 8 times the thickness of the first thermoplastic adhesive layer, counting from the magnetic substrate surface to the outside. The thickness of the outermost thermoplastic adhesive layer is increased to facilitate protection of each adhesive layer inside.
[0033] According to an alternative embodiment of the present invention, the thickness of the adhesive layer is adapted to the installation design. The total thickness of the adhesive layer can be 80 to 150 μm, which meets the adhesive performance while avoiding the wasteful consumption of adhesive.
[0034] According to an alternative embodiment of the invention, the ratio of the sum of all thicknesses of the thermosetting adhesive layers to the sum of all thicknesses of the thermoplastic adhesive layers is between 4 and 10:1.
[0035] According to another embodiment of the present invention, the thermoplastic adhesive of the thermoplastic adhesive layer includes a thermoplastic base agent, the thermoplastic base agent being an acrylic resin, the monomer for synthesizing the acrylic resin being acrylic acid and its derivatives, and the acrylic acid derivatives being urethane-modified ethyl methacrylate, urethane-modified methyl methacrylate, urethane-modified ethyl acrylate, n-butyl acrylate, hexyl methacrylate, hydroxyethyl acrylate, hydroxymethyl acrylate, etc. Examples of initiators used in the synthesis of the acrylic resin include benzoyl peroxide, t-amylperoxy-2-ethylhexyl acid ester, t-amylperoxybenzoate, etc.
[0036] The thermoplastic adhesive includes a thermoplastic base agent and a first auxiliary agent, the first auxiliary agent including nano-barium sulfate and nano-ethylene wax, among which the nano-barium sulfate can improve the hardness of the thermoplastic adhesive layer, and the nano-ethylene wax can improve the smoothness and blocking resistance of the thermoplastic adhesive layer, and can also improve the dispersibility of barium sulfate in the thermoplastic adhesive layer.
[0037] Alternatively, the blending ratio of the raw materials of the thermoplastic adhesive is 20 to 30% by weight of acrylic acid, 20 to 30% by weight of acrylic acid derivative, 5 to 18% by weight of initiator, 0.5 to 1% by weight of nano barium sulfate, and 0.5 to 1% by weight of nano ethylene wax, with the remainder being distilled water. The components and blending ratio of the thermoplastic adhesive can be appropriately adjusted as necessary.
[0038] According to another aspect of the present invention, the thermosetting adhesive of the thermosetting adhesive layer includes a thermosetting base material that is a thermosetting resin such as an epoxy resin, a phenolic resin, an unsaturated polyester resin, a silicone resin, or a modified acrylic resin. The thermosetting resin layer may include a plurality of resins. Epoxy resins are preferred, and may be cyclic, aliphatic, alicyclic, or aromatic. Suitable epoxy resins are preferably bisphenol A-based epoxy resins, bisphenol F-based epoxy resins, bisphenol S-based epoxy resins, phenol novolac-based epoxy resins, and aromatic epoxy resins (e.g., naphthalene skeleton-containing epoxy resins).
[0039] The blowing agent may be either a physical blowing agent or a chemical blowing agent, and in particular, expandable hollow microspheres are preferred. The expandable hollow microspheres may be composed of a shell made of a thermoplastic material and a low boiling point hydrocarbon enclosed in the shell. Furthermore, the shell material of the blowing agent is the same as the monomer material used to synthesize the thermoplastic main agent in the thermoplastic adhesive layer agent raw material. Preferred chemical blowing agents may be expanded graphite, ammonium polyphosphate, azodicarbonamide, and nanosilica-adsorbed N-aminoethylpiperazine (ATP).
[0040] The thermosetting adhesive of the thermosetting adhesive layer further includes a curing agent, a filler, and a second auxiliary agent.
[0041] The curing agent may be at least one of guanidine, substituted guanidine, aromatic amine, or guanylamine derivative. The curing agent may participate in the curing reaction in stoichiometric amounts and may be catalytically active. The substituted guanidine may be selected from methylguanidine, dimethylguanidine, trimethylguanidine, tetramethylguanidine, dimethylisobiguanide, tetramethylisobiguanide, cyanoguanidine, with cyanoguanidine being preferred.
[0042] The filler is at least one of silica, calcium oxide, zinc oxide, magnesium oxide, alumina, calcium carbonate, and talc.
[0043] The second auxiliary agent is at least one of a curing accelerator, a coupling agent, an antifoaming agent, a fiber, a rubber particle, a diluent, and a flame retardant. Among them, the curing accelerator may be an imidazole derivative (e.g., 2-ethyl-2-methylimidazole, N-butylimidazole), or a tertiary amine (e.g., 2-dimethylaminoethanol, N-substituted piperazine). The rubber may be selected from nitrile rubber particles, which further reduces the risk of cracking of the adhesive layer. The fiber may be selected from carbon fiber, metal fiber, glass fiber, polyester fiber, etc., which may increase the strength and toughness of the adhesive layer.
[0044] The raw materials for synthesizing the thermosetting adhesive layer consist of 70-80 wt% of the thermosetting base agent, 1-5 wt% of the foaming agent, 1-3 wt% of the curing agent, 2-6 wt% of the filler, and the remainder of the second auxiliary agent. The expansion rate of the adhesive layer can be adjusted by adjusting the content of the expansion agent.
[0045] A suitable amount of a solvent may be added to the thermosetting adhesive of the thermosetting adhesive layer, such as acetone, methyl ethyl ketone, toluene, benzene, or cyclohexanone.
[0046] The present invention also provides a method for producing the above-mentioned magnet with an adhesive layer, which comprises: S110, a preparation step: mixing an expansion agent into a thermosetting adhesive as a raw material for a thermosetting adhesive layer.
[0047] S120, coating step: one or more adhesive layers are applied from the surface of the magnet base outward in sequence. The adhesive layers include a thermosetting adhesive layer and a thermoplastic adhesive layer provided on the thermosetting adhesive layer, the thermosetting adhesive layer is disposed closer to the surface of the magnet base than the thermoplastic adhesive layer, the thermosetting adhesive layer is subjected to a low-temperature surface drying treatment, and the thermoplastic adhesive layer is subjected to a low-temperature curing treatment.
[0048] The adhesive layer is formed by applying a thermosetting adhesive layer and a thermoplastic adhesive layer. The number of adhesive layers may be one or more.
[0049] When there is a single adhesive layer, a thermosetting adhesive layer is applied to the surface of the magnet base, and a thermoplastic adhesive layer is further applied to the surface of the thermosetting adhesive layer to form an adhesive layer.
[0050] In the case of a multi-layer adhesive layer, a thermosetting adhesive layer and a thermoplastic adhesive layer are alternately applied from the surface of the magnet base toward the outside to form a multi-layer adhesive layer. By alternately applying a multi-layer of thermosetting adhesive layers and thermoplastic adhesive layers, the compatibility between the thermosetting adhesive layers and the thermoplastic adhesive layers can be improved while the adhesive strength of the adhesive layers themselves can be improved.
[0051] The thermosetting adhesive layer is subjected to a low-temperature surface drying treatment. The low-temperature surface drying treatment refers to drying the surface of the thermosetting adhesive layer at 40 to 90°C to facilitate application of the thermoplastic adhesive layer. All thermoplastic adhesive layers were subjected to a low-temperature hardening treatment. The low-temperature hardening treatment refers to hardening the thermoplastic adhesive layer at 40 to 90°C.
[0052] According to an alternative embodiment of the invention, the total thickness of the adhesive layers is between 80 and 150 μm.
[0053] According to an alternative embodiment of the present invention, when the adhesive layer is applied in multiple layers, the ratio of the thickness of the thermoplastic adhesive layer of the outermost layer to the thickness of the thermoplastic adhesive layer of any remaining layers is 2:1 to 8:1.
[0054] According to an alternative embodiment of the present invention, the ratio of the sum of all thicknesses of the thermosetting adhesive layers to the sum of all thicknesses of the thermoplastic adhesive layers is 4:1 to 10:1, and the gradually expanded thermosetting adhesive layers rupture the thermoplastic adhesive layers and encapsulate the ruptured thermoplastic adhesive layers.
[0055] According to an alternative embodiment of the present invention, when the number of thermosetting adhesive layers is only one, the thickness of the thermosetting adhesive layer may be relatively large, and the raw material can be applied multiple times to form the thermosetting adhesive layer. During application of the thermosetting adhesive layer, the thickness of the thermosetting adhesive layer is not too thick, and a large amount of moisture or solvent is not mixed into the thermosetting adhesive layer, which adversely affects the curing of the thermosetting resin adhesive layer.
[0056] Specifically, the raw material for the thermosetting adhesive layer is applied, the raw material for the first thermosetting adhesive layer is subjected to a low-temperature surface drying process, and then the raw material for the second thermosetting adhesive layer is subjected to a low-temperature surface drying process, and this is continued until the thickness of the thermosetting adhesive layer reaches a predetermined value.
[0057] According to another embodiment of the present invention, before the coating step, a monomer for synthesizing a thermoplastic base agent, an initiator, and a first auxiliary agent are mixed in distilled water as raw materials for the thermoplastic adhesive layer.
[0058] According to an alternative aspect of the invention, before the preparation step, the blowing agent is pretreated with monomers which synthesize the thermoplastic base. When the blowing agent is a physical blowing agent, if the shell material of the blowing agent and the thermoplastic base material of the thermoplastic adhesive layer are different, the blowing agent is modified with a monomer of the thermoplastic base material prior to the preparation step.
[0059] The modification process is a process in which the shell material of the expansion agent is modified by chemical group grafting using a monomer of the thermoplastic base.
[0060] When the blowing agent is a chemical blowing agent, the monomer of the thermoplastic base and the blowing agent are emulsified. The emulsion is prepared by mixing the monomer of the thermoplastic base pretreated with the blowing agent, adding a conventional emulsifier, such as monoglyceride, fatty acid ester, etc., and mechanically stirring to form an emulsion with good dispersibility and stability.
[0061] In the preparation, the pretreated expanding agent is mixed into the thermosetting adhesive to form the raw material for the thermosetting adhesive layer.
[0062] The pretreatment with the expansion agent is advantageous in improving the interfacial compatibility between the thermosetting adhesive and the thermoplastic adhesive by the expansion agent.
[0063] If the shell material of the expanding agent and the thermoplastic base material of the thermoplastic adhesive layer are the same, the pretreatment step is omitted.
[0064] The magnet with adhesive layer of the present invention can be stored and / or transported from the application site to the bonding site without applying adhesive to the assembly site where the magnet is installed, eliminating the need to use liquid adhesive at the part manufacturing site and avoiding problems of contact with liquid and contamination due to a lack of adhesive.
[0065] The present invention further provides a method for manufacturing a magnet assembly. The magnet assembly is made using a carrier and a magnet with an adhesive layer as described above. The carrier comprises a housing vessel for the magnet. Optionally, the carrier is a rotor or a stator of a motor. The preparation method includes: S210: The magnet with the adhesive layer was inserted into the carrier container.
[0066] S220: The carrier is heated to 150 to 200°C, the expanding agent is expanded to crosslink and cure the thermosetting adhesive layer, and the thermosetting adhesive layer is mixed and copolymerized with the thermoplastic adhesive layer, and the heated adhesive layer is filled between the wall of the carrier storage tank and the magnet base.
[0067] At this temperature of 150 to 200°C, the thermoplastic adhesive layer becomes soft. The gradually expanded thermosetting adhesive layer bursts the thermoplastic adhesive layer and wraps around the burst thermoplastic adhesive layer. Under this temperature condition of 150 to 200°C, the thermosetting adhesive not only crosslinks and hardens by itself, but also forms a stable crosslinked structure by blending and copolymerizing with the thermoplastic adhesive. In particular, when the magnet is placed in the carrier storage tank and the thermosetting adhesive is expanded, it is pressed against the inner wall of the tank and refluxed, and the phenomenon that the thermosetting adhesive of the inner layer wraps around the thermoplastic adhesive of the outer layer becomes prominent, and the bonding between the magnet and the carrier is ensured.
[0068] Word Interpretation: In this application, "adhesive" means having a property such that the magnet structure disposed on the carrier does not slip off or fall off under the influence of forces generated by gravity or assembly-related operations before the adhesive layer hardens.
[0069] Here, "swelling ratio" means that when heat is applied, the adhesive layer swells and the volume of the adhesive layer increases by the following formula: swelling ratio (%) = (adhesive layer thickness after swelling - adhesive layer thickness before swelling) / adhesive layer thickness before swelling).
[0070] In this application, the "shrinkage rate" means that the thickness of the adhesive layer after expansion partially shrinks under high temperature conditions, and is characterized by the change in thickness of the adhesive layer before and after expansion under constant high temperature conditions in order to test the resistance of the adhesive layer after expansion to high temperatures, where the shrinkage rate (%) = (thickness of adhesive layer after expansion - thickness of adhesive layer after constant high temperature treatment) / thickness of adhesive layer after expansion.
[0071] The blending ratio of the thermosetting adhesive layer raw material and the thermoplastic adhesive layer raw material in the examples is as follows: Table 1 Raw materials for thermosetting adhesive layer (100% by weight) TIFF0007635388000001.tif88170 Table 2 Thermoplastic adhesive layer raw material (100% by weight) TIFF0007635388000002.tif84170Here, the shell material of the expanding agent is the same as the thermoplastic base material.
[0072] Example 1 A method of manufacturing magnets and magnet assemblies comprising the steps of: Preparation process: A thermosetting adhesive layer raw material A-1 was prepared based on Table 1, and a thermoplastic adhesive layer raw material B-1 was prepared based on Table 2.
[0073] Application process: Thermosetting adhesive layer raw material A-1 was applied to the surface of the magnet base, and the surface was dried at 40° C., after which thermoplastic adhesive layer raw material B-1 was applied onto the thermosetting adhesive layer and cured at 40° C. to obtain a magnet having an adhesive layer on its surface. Here, the thickness of the thermosetting adhesive layer was 80 μm, the thickness of the thermoplastic adhesive layer was 20 μm, and the thickness of the adhesive layer was 100 μm.
[0074] The magnet with the adhesive layer is inserted into the housing of the motor rotor.
[0075] The carrier was heated to 150° C. to expand the expanding agent, crosslinking and curing the thermosetting adhesive layer, and blending and copolymerizing it with the thermoplastic adhesive layer.
[0076] Example 2 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-1 was prepared based on Table 1, and thermoplastic adhesive layer raw material B-1 was prepared based on Table 2.
[0077] 2. The thermosetting adhesive layer raw material A-1 is applied to the surface of the magnet base and the surface is dried at 40°C to form a 40μm first layer thermosetting adhesive layer, the thermosetting adhesive layer raw material A-1 is again applied to the surface of the first layer thermosetting adhesive layer raw material and the surface is dried at 40°C to form a 40μm second layer thermosetting adhesive layer, and then 20μm of thermoplastic adhesive layer raw material B-1 is applied and cured at 40°C to obtain a magnet with an adhesive layer on the surface. Here, the total thickness of the thermosetting adhesive layer including the 40μm first layer thermosetting adhesive layer and the 40μm second layer thermosetting adhesive layer is 80μm, the thickness of the thermoplastic adhesive layer is 20μm, and the thickness of the adhesive layer is 100μm.
[0078] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0079] 4. The carrier is heated to 150°C to expand the expansion agent, crosslink and cure the thermosetting adhesive layer, and blend and copolymerize with the thermoplastic adhesive layer.
[0080] Example 3 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-1 was prepared based on Table 1, and thermoplastic adhesive layer raw material B-1 was prepared based on Table 2.
[0081] 2. Coat the surface of the magnet base with thermosetting adhesive layer raw material A-1 and dry the surface at 40°C to form a first layer of thermosetting adhesive layer with a thickness of 40 μm; coat the thermoplastic adhesive layer raw material B-1 on the first layer of thermosetting adhesive layer and dry it at 40°C to form a first layer of thermoplastic adhesive layer with a thickness of 5 μm; coat the thermosetting adhesive layer raw material A-1 on the first layer of thermoplastic adhesive layer and dry it at 40°C to form a second layer of thermosetting adhesive layer with a thickness of 40 μm; coat the thermoplastic adhesive layer raw material B-1 on the second layer of thermosetting adhesive layer and dry it at 40°C to form a second layer of thermoplastic adhesive layer with a thickness of 15 μm; obtain a magnet with an adhesive layer on its surface. Here, the total thickness of the thermosetting adhesive layer including the first thermosetting adhesive layer of 40 μm and the second thermosetting adhesive layer of 40 μm is 80 μm, the thickness of the thermoplastic adhesive layer including the first thermoplastic adhesive layer of 5 μm and the second thermoplastic adhesive layer of 15 μm is 20 μm, and the thickness of the adhesive layer is 100 μm.
[0082] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0083] 4. The carrier is heated to 150°C to expand the expansion agent, crosslink and cure the thermosetting adhesive layer, and blend and copolymerize with the thermoplastic adhesive layer.
[0084] Example 4 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-2 was prepared according to Table 1, and thermoplastic adhesive layer raw material B-2 was prepared according to Table 2.
[0085] 2. Apply thermosetting adhesive layer raw material A-2 to the surface of the magnet base, dry the surface at 60°C, and form a 35μm first layer thermosetting adhesive layer; apply thermosetting adhesive layer raw material A-2 again to the surface of the first layer thermosetting adhesive layer raw material, dry the surface at 60°C, and then form a 35μm second layer thermosetting adhesive layer; apply thermoplastic adhesive layer raw material B-2 on the second layer thermosetting adhesive layer, and harden at 60°C to form a 10μm thermoplastic adhesive layer; obtain a magnet with an adhesive layer on its surface. Here, the total thickness of the thermosetting adhesive layer including the 35μm first layer thermosetting adhesive layer and the 35μm second layer thermosetting adhesive layer is 70μm, the thickness of the thermoplastic adhesive layer is 10μm, and the thickness of the adhesive layer is 80μm.
[0086] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0087] 4. The carrier is heated to 180°C to expand the expansion agent, crosslink and cure the thermosetting adhesive layer, and blend and copolymerize with the thermoplastic adhesive layer.
[0088] Example 5 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-2 was prepared according to Table 1, and thermoplastic adhesive layer raw material B-2 was prepared according to Table 2.
[0089] 2. Apply thermosetting adhesive layer raw material A-2 on the surface of the magnet base and dry the surface at 90°C to form a first layer of 60μm thermosetting adhesive layer; apply thermosetting adhesive layer raw material A-2 again on the surface of the first layer of thermosetting adhesive layer raw material and dry the surface at 90°C, then form a second layer of 60μm thermosetting adhesive layer; apply thermoplastic adhesive layer raw material B-2 on the two layers of thermosetting adhesive layer and harden at 90°C to form a thermoplastic adhesive layer of 30μm; obtain a magnet with an adhesive layer on the surface. Here, the total thickness of the thermosetting adhesive layer including the first layer of 60μm thermosetting adhesive layer and the second layer of 60μm thermosetting adhesive layer is 120μm, the thickness of the thermoplastic adhesive layer is 30μm, and the thickness of the adhesive layer is 150μm.
[0090] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0091] 4. The foaming agent was expanded by heating to 200°C, the thermosetting adhesive layer was crosslinked and cured, and the thermosetting adhesive layer was blended and copolymerized with the thermoplastic adhesive layer.
[0092] Example 6 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Based on Table 1, urethane-modified ethyl acrylate and ATP were mixed, monodiglyceride was added, and the mixture was mechanically stirred to form an emulsion, which was then mixed into a thermosetting adhesive to prepare thermosetting adhesive layer raw material A-3. Based on Table 2, thermoplastic adhesive layer raw material B-3 was prepared.
[0093] 2. Thermosetting adhesive layer raw material A-3 is applied to the surface of the magnet base and the surface is dried at 50°C to form a first thermosetting adhesive layer of 45 μm; thermoplastic adhesive layer raw material B-3 is applied on the first thermosetting adhesive layer and cured at 50°C to form a first thermoplastic adhesive layer of 4 μm; thermosetting adhesive layer raw material A-3 is applied on the first thermoplastic adhesive layer and the surface is dried at 50°C to form a second thermosetting adhesive layer of 45 μm; thermoplastic adhesive layer raw material B-3 is applied on the second thermosetting adhesive layer and cured at 50°C to form a second thermoplastic adhesive layer of 16 μm; a magnet with an adhesive layer on its surface is obtained. Here, the total thickness of the thermosetting adhesive layer including the first thermosetting adhesive layer of 45 μm and the second thermosetting adhesive layer of 45 μm is 90 μm, the thickness of the thermoplastic adhesive layer including the first thermoplastic adhesive layer of 4 μm and the second thermoplastic adhesive layer of 16 μm is 20 μm, and the thickness of the adhesive layer is 110 μm.
[0094] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0095] 4. The thermosetting adhesive layer was heated at 160°C to expand the expansion agent, crosslink and cure it, and then blended and copolymerized with the thermoplastic adhesive layer.
[0096] Example 7 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Based on Table 1, urethane-modified ethyl acrylate and ATP were mixed, monodiglyceride was added, and the mixture was mechanically stirred to form an emulsion, which was then mixed into a thermosetting adhesive to prepare thermosetting adhesive layer raw material A-3. Based on Table 2, thermoplastic adhesive layer raw material B-3 was prepared.
[0097] 2. Coat the surface of the magnet base with thermosetting adhesive layer raw material A-3 and dry the surface at 50°C to form a first layer of 30μm thermosetting adhesive layer; coat the thermoplastic adhesive layer raw material B-3 on the first layer of thermosetting adhesive layer and dry at 50°C to form a first layer of 2μm thermoplastic adhesive layer; coat the thermosetting adhesive layer raw material A-3 on the first layer of thermoplastic adhesive layer and dry at 50°C to form a second layer of 30μm thermosetting adhesive layer; coat the second layer of thermosetting adhesive layer with A step of applying thermoplastic adhesive layer raw material B-3 onto the thermoplastic adhesive layer and curing it at 50°C to form a 2 μm second layer thermoplastic adhesive layer; applying thermosetting adhesive layer raw material A-3 onto the second layer thermoplastic adhesive layer and drying it at 50°C to form a 30 μm third layer thermosetting adhesive layer; applying thermoplastic adhesive layer raw material B-3 onto the third layer thermosetting adhesive layer and curing it at 50°C to form a 16 μm third layer thermoplastic adhesive layer; obtaining a magnet with an adhesive layer on its surface. Here, the total thickness of the thermosetting adhesive layer including the 30 μm first layer thermosetting adhesive layer, the 30 μm second layer thermosetting adhesive layer, and the 30 μm third layer thermosetting adhesive layer is 90 μm, the thickness of the thermoplastic adhesive layer is 20 μm, and the thickness of the adhesive layer is 110 μm.
[0098] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0099] 4. The foaming agent was expanded by heating to 170°C, the thermosetting adhesive layer was crosslinked and cured, and the thermosetting adhesive layer was blended and copolymerized with the thermoplastic adhesive layer.
[0100] Example 8 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-4 was prepared according to Table 1, and thermoplastic adhesive layer raw material B-4 was prepared according to Table 2.
[0101] 2. Apply thermosetting adhesive layer raw material A-4 on the surface of the magnet base, dry the surface at 40°C, and form a 50μm first layer thermosetting adhesive layer; apply thermosetting adhesive layer raw material A-4 again on the surface of the first layer thermosetting adhesive layer raw material, dry the surface at 40°C, and then form a 50μm second layer thermosetting adhesive layer; apply thermoplastic adhesive layer raw material B-4 on the second layer thermosetting adhesive layer, and harden at 40°C to form a 10μm thermoplastic adhesive layer; obtain a magnet with an adhesive layer on its surface. Here, the total thickness of the thermosetting adhesive layer including the 50μm first layer thermosetting adhesive layer and the 50μm second layer thermosetting adhesive layer is 100μm, the thickness of the thermoplastic adhesive layer is 10μm, and the thickness of the adhesive layer is 110μm.
[0102] 3. The magnet with adhesive layer is inserted into the housing of the motor rotor.
[0103] 4. The carrier is heated to 150°C to expand the expansion agent, crosslink and cure the thermosetting adhesive layer, and blend and copolymerize with the thermoplastic adhesive layer.
[0104] Comparative Example 1 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Based on Table 2, the expansion agent of Example 1 was mixed into the thermoplastic adhesive layer raw material B-1 in the same mass ratio to prepare an adhesive layer raw material.
[0105] 2. Coat the adhesive layer material on the surface of the magnet base and harden it at 40℃ to form a 20μm adhesive layer; coat the adhesive layer material on the surface of this adhesive layer material again and harden it at 40℃ to form a 20μm adhesive layer. Repeat this process 5 times to obtain a magnet with a thermoplastic adhesive layer on the surface. The total thickness of the thermoplastic adhesive layer was 100μm.
[0106] 3. The magnet with adhesive layer is inserted into the receiving tub of the motor rotor.
[0107] 4. The carrier was heated to 150°C to expand the expansion agent.
[0108] Comparative Example 2 A method of manufacturing magnets and magnet assemblies comprising the steps of: 1. Thermosetting adhesive layer raw material A-1 was prepared based on Table 1.
[0109] 2. The thermosetting adhesive layer raw material A-1 was applied to the surface of the magnet base, and the surface was dried at 40°C to form a first thermosetting adhesive layer of 80 μm; the thermosetting adhesive layer raw material A-1 was again applied to the surface of the first thermosetting adhesive layer raw material, and the surface was dried at 40°C to form a second thermosetting adhesive layer of 20 μm. A magnet body having a thermosetting adhesive layer on its surface was obtained. The thickness of the thermosetting adhesive layer including the first thermosetting adhesive layer of 80 μm and the second thermosetting adhesive layer of 20 μm was 100 μm.
[0110] 3. The magnet with the thermosetting adhesive layer is inserted into the receiving tub of the motor rotor.
[0111] 4. The carrier was heated to 150°C to expand the expansion agent.
[0112] A performance test was carried out to compare the properties of the adhesive layer after thermal expansion between the examples and the comparative examples, and the results are shown in Table 3. Item 1: 50 magnets with adhesive layers were stacked vertically for 48 hours.
[0113] Item 2: After leaving the magnet with the adhesive layer for half a year, it was heated at 180°C for 30 minutes and the swelling rate (%) of the adhesive layer was calculated.
[0114] Item 3: The shrinkage rate of the adhesive layer after heating a magnet with an adhesive layer at 180°C for 30 minutes to expand the adhesive layer, and then baking it at 180°C for 196 hours.
[0115] Item 4: A magnet with adhesive was placed in the motor's storage tank and heated at 180°C for 30 minutes to swell the adhesive layer, and the peel strength (N / mm) of the adhesive layer from the tank wall was measured at room temperature.
[0116] 5: The magnet with adhesive was placed in the motor's storage tank and heated at 180°C for 30 minutes to swell the adhesive layer, and the peel strength (N / mm) of the adhesive layer from the tank wall was measured at 160°C.
[0117] Item 6: Neutral salt spray test (h).
[0118] Item 7: PCT test (high pressure accelerated aging life test) (h) The test conditions are a temperature of 120°C, a relative humidity of 100%, and a pressure of 2 atm.
[0119] Test results in Table 3 TIFF0007635388000003.tif114170In item 1 of Table 3, no adhesion means no adhesion between magnets, showing no adhesion on the magnet surface; slight adhesion means slight adhesion between magnets, showing slight stickiness on the magnet surface; severe sticking means severe sticking between magnets, not considering the application, so the following test was not performed.
[0120] As a result of analyzing the above test results, it was found that the main factor affecting the volume of the adhesive layer after expansion is the expansion agent. The adhesive layer obtained by applying a thermosetting adhesive layer in multiple separate applications or by repeatedly applying a thermosetting adhesive layer and a thermoplastic adhesive layer multiple times has a high expansion efficiency, and the adhesive strength of the adhesive layer itself and the adhesive strength to the magnetic substrate and the storage tank wall are high. The magnet manufactured by the present invention was taken out after measuring 200h in the PCT experiment, and there was no change in the adhesive layer on the magnet surface, but the magnet of Comparative Example 1 was measured for 80h, and a foaming phenomenon occurred in the adhesive layer on the magnet surface, indicating that the magnet manufactured by the present invention has excellent high temperature resistance and corrosion prevention performance. In addition, the test results show that the adhesive layer manufactured by the present invention has excellent adhesion between the magnet and the carrier member, and the shrinkage rate at 180°C of the adhesive layer manufactured by the present invention is less than 5%, indicating that the effect of the use temperature on the swelling behavior of the adhesive layer is small.
[0121] The above is a detailed description of the embodiments of the present invention. The principles and embodiments of the present invention are described in the present specification by applying specific examples. However, the above description of the embodiments is merely intended to facilitate understanding of the technical solution and core idea of the present invention. Therefore, when a person skilled in the art practices the present invention based on the idea of the present invention, any changes or modifications in the specific embodiments and application scope of the present invention also fall within the scope of the present invention. In view of the above, the contents of this specification should not be construed as limiting the present application.
Claims
1. The magnetic material comprises a magnetic substrate and at least one adhesive layer, the first adhesive layer being provided on the surface of the magnetic substrate; the adhesive layer includes a thermosetting adhesive layer and a thermoplastic adhesive layer, the thermosetting adhesive layer being closer to the magnet substrate surface than the thermoplastic adhesive layer; The thermosetting adhesive layer contains an expanding agent, A magnet with an adhesive layer, wherein the thermoplastic adhesive layer is cured under conditions of 40°C to 90°C to form a non-adhesive thin layer.
2. The number of the adhesive layers is plural, and the adhesive layers are provided in order from the surface of the magnet base toward the outside, A magnet with an adhesive layer as described in claim 1, characterized in that the ratio of the thickness of the outermost thermoplastic adhesive layer to the thickness of any one of the remaining thermoplastic adhesive layers is 2:1 to 8:
1.
3. 2. The magnet with adhesive layers according to claim 1, wherein the total thickness of the adhesive layers is 80 to 150 μm.
4. A magnet with an adhesive layer as described in claim 1, characterized in that the ratio of the sum of the thicknesses of all of the thermosetting adhesive layers to the sum of the thicknesses of all of the thermoplastic adhesive layers is 4:1 to 10:
1.
5. 2. The magnet with adhesive layer according to claim 1, wherein the thermoplastic adhesive layer includes a first additive having nano-barium sulfate and nano-ethylene wax.
6. The thermosetting adhesive layer includes a curing agent, a filler, and a second auxiliary agent, the curing agent is at least one of guanidine, substituted guanidine, aromatic amine, and guanylamine derivative; the filler is at least one of silica, calcium oxide, zinc oxide, magnesium oxide, aluminum oxide, calcium carbonate, and talc; 2. The magnet with an adhesive layer according to claim 1, characterized in that the second auxiliary agent is at least one of a curing accelerator, a coupling agent, an antifoaming agent, a fiber, a rubber particle, a diluent, and a flame retardant.
7. A method for manufacturing a magnet having an adhesive layer, comprising: Preparation step: A step of preparing a thermosetting adhesive layer by mixing an expanding agent into the thermosetting adhesive; A coating step: coating at least one adhesive layer from the surface of the magnet substrate outward in sequence; A method for manufacturing a magnet having an adhesive layer, characterized in that the adhesive layer consists of a thermosetting adhesive layer and a thermoplastic adhesive layer, the thermosetting adhesive layer is positioned closer to the surface of the magnet base than the thermoplastic adhesive layer, the thermosetting adhesive layer is subjected to a surface drying treatment at 40°C to 90°C, and the thermoplastic adhesive layer is subjected to a hardening treatment at 40°C to 90°C.
8. The method for producing a magnet with an adhesive layer according to claim 7, characterized in that the total thickness of the adhesive layers is 80 to 150 μm.
9. The method for manufacturing a magnet with an adhesive layer, as described in claim 7, characterized in that when the adhesive layer is applied in multiple layers in the application process, the ratio of the thickness of the outermost thermoplastic adhesive layer to the thickness of any remaining thermoplastic adhesive layer is 2:1 to 8:
1.
10. The method for manufacturing a magnet with an adhesive layer as described in claim 7, characterized in that the ratio of the sum of the thicknesses of all the thermosetting adhesive layers to the sum of the thicknesses of all the thermoplastic adhesive layers is 4:1 to 10:
1.
11. Before the coating step, a monomer for synthesizing a thermoplastic base agent, an initiator, and a first assistant agent are mixed with distilled water as raw materials for the thermoplastic adhesive layer; The method for producing a magnet with an adhesive layer according to claim 7 .
12. When the thermosetting adhesive layer is only one layer, the thermosetting adhesive layer is formed by applying the raw material of the thermosetting adhesive layer multiple times; 8. The method for producing a magnet with an adhesive layer according to claim 7, further comprising the steps of:
13. Prior to the preparation step, the expanding agent is pretreated with a monomer that synthesizes a thermoplastic base; In the preparation, the pretreated expanding agent is mixed into the thermosetting adhesive to form the raw material for the thermosetting adhesive layer. The method for producing a magnet with an adhesive layer according to claim 7 .
14. A method for producing a magnet assembly produced using a carrier and a magnet with an adhesive layer according to any one of claims 1 to 6, the method comprising: Insertion: inserting the magnet with the adhesive layer into the receiving vessel of the carrier; Heating: The adhesive layer is heated to expand the expansion agent, crosslink and cure the thermosetting adhesive layer, blend and copolymerize the thermoplastic adhesive layer and the thermosetting adhesive layer, and fill the space between the wall of the carrier housing tank and the magnet base with the heated adhesive layer.
15. A magnet assembly manufactured by the method of claim 14.
Citation Information
Patent Citations
Melt flowable material and surface sealing method
JP1999503482A
Anisotropic bonded magnet assembly, its manufacturing method, and permanent magnet motor using the magnet assembly
JP2007028725A
Clear-coated stainless steel plate and its manufacturing method
JP2008149607A
Adhesive sheet
JP2016084470A
Adhesive tape, article, motor and method for manufacturing the article
JP2017052950A